Healthcare transition from childhood to adulthood in Tuberous Sclerosis Complex. Issue 3 (25th September 2018) - Peron, Angela; Canevini, Maria Paola; Ghelma, Filippo; Di Marco, Fabiano; Vignoli, Aglaia
Abstract : Healthcare transition from childhood to adulthood is required to ensure continuity of care of an increasing number of individuals with chronic conditions surviving into adulthood. The transition for patients with tuberous sclerosis complex (TSC) is complicated by the multisystemic nature of this condition, age‐dependent manifestations, and high clinical variability and by the presence of intellectual disability in at least half of the individuals. In this article, we address the medical needs regarding each TSC‐related manifestation in adulthood, and the services and support required. We review existing models of transition in different chronic conditions, discuss our experience in transitioning from the pediatric to the adult TSC Clinic at our Institution, and propose general rules to follow when establishing a transition program for TSC. Although a generalizable transition model for TSC is likely not feasible for all Institutions, a multidisciplinary TSC clinic is probably the best model, developed in accordance with the resources available and country‐specific healthcare systems. Coordination of care and education of the adult team should be always sought regardless of the transition model.